Production control policy for manufacturing systems with multiple server stations and time constraints between two consecutive operations - Leoga Proklamanus. (2013)
In a production system, achieving a high productivity with lowest cost is one of the overall goals. However, to maintain the quality of the product, usually a time constrain is assigned to the product where the product is considered fail if is it allowed to queue longer than the time constrain. The "fail" product is either reworked or scrapped. Rework and loss (scrap) will reduce the productivity and increase the production cost.